DAYA SERAP ARANG AKTIF TONGKOL JAGUNG SEBAGAI MEDIA FILTER DALAM MENURUNKAN KADAR BESI (Fe) PADA AIR - Suwantiningsih, Suwantiningsih; Khambali, Kahmbali; Narwati, Narwati (Poltekkes Kemenkes Tanjung Karang, 2020)
Corn cobs are a solid waste that has not been maximally utilized and can pollute the environment. Corn cobs can be used as activated charcoal because they contain cellulose (41%) and hemicellulose (36%). The research objective was to determine the ability of corncob activated charcoal to reduce water iron (Fe) content in water.True Experiment research with pretest-posttest design with control group design with 6 repetitions. The mass variation of corn cobs activated charcoal in the filter media used was 2,920 gr, 4,380 gr, and 5,840 gr. The number of samples of the artificial iron solution used for each repetition of each of the variations in the mass of the adsorbent was 7 litres so that the total required was 168 litres. The data obtained were analyzed using One Way Anova.The results showed the levels of Fe after treatment in the mass variation of activated charcoal cob 2920 g was 2.55 mg / L, at 4,380 g mass was 1.67 mg / L, and in the mass 5.840 g was 0.64 mg / L. The highest reduction efficiency in iron content was in the mass of 5,840 grams which was able to reduce Fe levels up to 85.70%.This study proves that activated corn cobs can be used as an absorbent to reduce levels of iron (Fe) in water.Â